Walking the Ojibwe path : a memoir in letters to Joshua - Wagamese, Richard (Seedbank (Minneapolis, Minn.), 2023)
"Ojibwe tradition calls for fathers to walk their children through the world, sharing the ancient understanding "that we are all, animate and inanimate alike, living on the one pure breath with which the Creator gave life to the Universe." In this new entry in the Seedbank series, an intimate series of letters to the six-year-old son from whom he was estranged, Richard Wagamese fulfills this traditional duty with grace and humility, describing his own path through life--separation from his family as a boy, substance abuse, incarceration, and ultimately the discovery of books and writing--and braiding this extraordinary story with the teachings of his people, in which animals were the teachers of human beings, until greed and a desire to control the more-than-human world led to anger, fear, and, eventually, profound alienation."--